Software Quality: Higher Software Quality through Zero Waste Development 15th International Conference, SWQD 2023, Munich, Germany, May 23-25, 2023, Proceedings - Mendez, Daniel; Winkler, Dietmar; Kross, Johannes; Biffl, Stefan; Bergsmann, Johannes (Cham : Springer Nature Switzerland : Imprint: Springer, 2023)
This book constitutes the refereed proceedings of the 15th Software Quality Days Conference, SWQD 2023, held in Munich, Germany, during May 23-25, 2023. The Software Quality Days (SWQD) conference started in 2009 and has grown to the biggest conference on software quality in Europe. The program of the SWQD conference is designed to encompass a stimulating mixture of practical presentations and new research topics in scientific presentations. The guiding conference topic of the SWQD 2023 is "Higher Software Quality through Zero Waste Development". The 4 full papers and 2 short papers presented in this volume were carefully reviewed and selected from 10 submissions. The volume also contains one invited talk.
Social Aspects in Software Engineering -- Conflicting Interests in the Hybrid Workplace: Five Perspectives to Consider -- Requirements Engineering -- Requirements Quality vs. Process and Stakeholders' Well-being: A Case of a Nordic Bank -- Software Defect Prediction -- Outlier Mining Techniques for Software Defect Prediction -- Software Testing -- Applying a Genetic Algorithm for Test Suite Reduction in Industry -- Software Metrics -- A catalog of source code metrics - a tertiary study -- Software Quality Assurance -- Software quality assessment: defect life cycle, software defect profile, its types and misalignments -- Comparing Anomaly Detection and Classification Algorithms: A Case Study in Two Domain.
Keywords: Software engineering; Software engineering -- Management; Artificial intelligence; Software Engineering; Software Management; Artificial Intelligence